2017
DOI: 10.1080/09687599.2017.1361385
|View full text |Cite
|
Sign up to set email alerts
|

The grace of motherhood: disabled women contending with societal denial of intimacy, pregnancy, and motherhood in Ethiopia

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research -You may not further distribute the material or use it for any profit-making activity or commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 45 publications
6
38
0
2
Order By: Relevance
“…Persons affected and their family members were sometimes socially excluded and insulted by their community members and divorce and difficulties in finding a spouse were not uncommon. Similar findings were found in a study on women with disabilities in Ethiopia, who experienced societal denial of marriage and motherhood [54]. Several studies among persons affected by leprosy, lymphatic filariasis and podoconiosis found high levels of stigma-for example among persons affected by podoconiosis in Ethiopia [17,20,29,52,[55][56][57][58][59].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 82%
“…Persons affected and their family members were sometimes socially excluded and insulted by their community members and divorce and difficulties in finding a spouse were not uncommon. Similar findings were found in a study on women with disabilities in Ethiopia, who experienced societal denial of marriage and motherhood [54]. Several studies among persons affected by leprosy, lymphatic filariasis and podoconiosis found high levels of stigma-for example among persons affected by podoconiosis in Ethiopia [17,20,29,52,[55][56][57][58][59].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 82%
“…For instance, Walsh-Gallagher and colleagues' study showed that WWDs perceived the experience of pregnancy and motherhood as one to celebrate, considered pregnancy an achievement, and felt that pregnancy resulted in a bonding experience and confidence in their ability to achieve a life goal [46]. One qualitative study from Ethiopia also reported that WWDs expressed their feelings of motherhood with a good spirit, with many considering motherhood as a source of joy [27].…”
Section: Discussionmentioning
confidence: 99%
“…What remains relatively underexplored is WWDs' motivations for childbearing. As some recent studies point out, very few studies have focused on understanding childbearing desires and motivations among WWDs, especially in low-income settings [2,23,27]. Similarly, while recent research highlights the role of attitudes, subjective norms and perceived behavioural control in the formation of fertility intentions in the general population [27], there is no specific focus on PWDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the opportunities and challenges that women with disabilities in low and middle income countries (LMICs) face in participating meaningfully in education, employment and family life (Tefera & Van Engen, 2016;Tefera, Van Engen, Van der Klink, & Schippers, 2017) is critical, not only to the articulation of inclusive development theories, but also to the design of appropriate (family) interventions to improve quality of life. While there has been increased interest in disability issues in developing countries, there is limited data available in this field (Loeb & Eide, 2008).…”
Section: Introductionmentioning
confidence: 99%